Basic COVID-19 knowledge according to education level and country of residence: Analysis of twelve countries in Latin America - Mejia, Christian R.; Aveiro-Robalo, Telmo Raul; Garlisi Torales, Luciana Daniela; Fernández, Maria Fernanda; Bonilla-Rodríguez, Francisco E.; Estigarribia, Enrique; Coronel-Ocampos, Johanna Magali; Caballero-Arzamendia, Cecilia J.; Torres, Renato R.; Conde-Escobar, Aram; Canaviri-Murillo, Yuliana; Castro-Pacoricona, Diana; et al. (Frontiers in Medicine, 2022)
Introduction: Knowing a disease is crucial for being able to fight it, especially in a region in which COVID-19 caused so many deaths, such as Latin America. Objective: To determine the association between basic knowledge of COVID-19 and education level according to country of residence in Latin America. Methodology: This is an analytical cross-sectional study. Basic level of knowledge was measured through nine close-ended questions (scale validated in Peru). The score obtained was analyzed through performing a crosstab versus gender, age, education level, and country of residence. Results: Of a total of 9222 respondents, almost all of them knew the common symptoms (99%), modes of transmission (93%), and knew how to recognize which was not a specific symptom (93%). Through the multivariate model, we found that there was no association with gender (p=0,716) or age (p=0,059), in comparison with those who had primary or a lower education level. All the other higher education levels had statistically significant scores (all p-values p < 0,001). When comparing knowledge according to countries, and using Peru as reference for comparison, Chile, Paraguay, Mexico, Bolivia, Panama, Ecuador, Costa Rica, and Colombia had a better level of knowledge (all p-values <0,001); however, only El Salvador had a lower level (p<0,001). Discussion: There was lack of knowledge of some topics, difference according to academic degree and country. As Peru was one of countries that obtained the lowest level of knowledge, it could have influenced the fact that it was the most affected country in the world.